2018
DOI: 10.22159/ajpcr.2018.v11i5.24296
|View full text |Cite
|
Sign up to set email alerts
|

Topical Drug Delivery for Effective Treatment of Bacterial Infections of the Anterior Segment of the Eye

Abstract: Anterior parts of the eye are susceptible to infections caused by different bacterial species. The use of suitable therapeutic measures in case of ocular infections can be sight saving. The appropriate therapy depends on selecting the right antibacterial as well as an efficient drug delivery system. Despite their accessibility, topical delivery of the selected antibiotic into the anterior ocular parts is still a challenging issue due to the complex nature of the eye. Ocular therapy would be significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Many studies have already demonstrated the potential of liposomes in increasing the corneal penetration and stability of ocular drugs [ 63 ]. Furthermore, Mishra et al found that contact lenses equipped with liposomes are capable of providing a stable release of antibiotic over six days, which was effective against S. aureus in vitro [ 69 ]. Figure 4 illustrates the structural differences between microemulsions and liposomes.…”
Section: Novel Therapeuticsmentioning
confidence: 99%
“…Many studies have already demonstrated the potential of liposomes in increasing the corneal penetration and stability of ocular drugs [ 63 ]. Furthermore, Mishra et al found that contact lenses equipped with liposomes are capable of providing a stable release of antibiotic over six days, which was effective against S. aureus in vitro [ 69 ]. Figure 4 illustrates the structural differences between microemulsions and liposomes.…”
Section: Novel Therapeuticsmentioning
confidence: 99%